Nigeria : Poverty Reduction Strategy Paper; National Economic Empowerment and Development Strategy. (IMF Staff Country Reports; Country Report ;, 2005)
This Poverty Reduction Strategy Paper for Nigeria highlights the National Economic Empowerment and Development Strategy (NEEDS). NEEDS gives special support to agriculture, industry, small and medium-scale enterprises, and oil and gas. Under the plan, the government will seek long-term capital for investment. Trade policy will be modified to unburden business of the red tape and complex procedures that hinder it from flourishing. NEEDS envisages forging stronger links between educational institutions and industry to stimulate rapid industrial growth and efficient exploitation of resources.